The TOR Regulatory Mechanism Controls the Metabolism of Nitrate and the Fermentation Activity in the Yeast Dekkera bruxellensis GDB 248 - Karolini Miranda; Beatriz Câmara de Melo; Gilberto Henriques Teles; Irina Charlot Peña-Moreno; Rafael Barros de Souza; Marcos Antonio de Morais (Microbiology Research, 2025)
Dekkera bruxellensis is already known for its great biotechnological potential, part of this due to the ability to assimilate nitrate during fermentation. Despite the previous works on nitrogen metabolism in this yeast, especially regarding nitrate assimilation, the relation between this metabolism and the TOR (Target of Rapamycin) regulatory mechanism remains unexplored. This connection may reveal key regulatory mechanisms to maximize its fermentative performance and biotechnological use. Herein, we evaluated the physiological, metabolic, and gene expression profile of D. bruxellensis GDB 248 cultivated in ammonium and nitrate as nitrogen sources in the presence of TOR complex 1 (TORC1) inhibitor rapamycin. Our results showed that inhibition of the TORC1 significantly reduces cell growth and fermentative capacity, especially in nitrate media. Gene expression analysis revealed that TORC1 plays a central role in regulating genes involved in nitrate assimilation and the adaptive performance of D. bruxellensis in fermentative environments. Therefore, the regulation of nitrate assimilatory genes YNTI, YNRI, and YNI1 responds to a nitrate-dependent mechanism as well as to a TOR-dependent mechanism. These findings expand the understanding of the regulation of nitrogen metabolism in D. bruxellensis, providing valuable information that may aid in the development of future strategies for its use as an industrial yeast.